Introducing catchment management: the case of South Africa - Elke Herrfahrdt-Pähle (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Climate change poses a major threat for a country like South Africa, which depends heavily on surface water and whose water resources are already under stress. Against this background one possible adaptation measure is a holistic approach and the management of water according to the basin principle. This paper examines current water sector reforms and especially the transition from administrative to hydrological boundaries. It concludes that this transition might serve as a building block for making the South African water governance system more adaptive to climate change. However, the analysis shows that the transition towards hydrological boundaries is afflicted with a number of trade-offs. These are firstly the trade-off between (1) the improved fit between the social and the ecological system and (2) the misfit between scales within the social system. Secondly a trade-off exists between (1) a correct classification along hydrological boundaries (holistic approach) and (2) a feasible size for effective management, meaningful stakeholder participation and financial viability, which may require a splitting and merging of hydrological entities and thus a violation of the hydrological principle. These trade-offs can only be met through a combination of intense communication, cooperation and coordinated action between the involved organisations.
Keywords: 330